Synthesis, Characterization and Preliminary Anti-Microbial Evaluation of New Flurbiprofen Hydrazide Derivatives - Hawraa Yusur Jassim; Mohammed Kamil Hadi (Iraqi Journal of Pharmaceutical Sciences, 2025)
A new series of 2-(2-fluoro-[1,1’-biphenyl]-4-yl)propanoic acid derivatives were synthesized to enhance their Anti-Microbial activities. The new flurbiprofen hydrazon compounds (4a-e) prepared by reacting flurbiprofen ethyl ester with hydrazine hydrate to yield flurbiprofen hydrazid(3). Then compound (3) reacted with several aromatic aldehydes in absolute ethanol in presence of a small amount of glacial acetic acid to yield final compounds (4a-e). Each final compound was examined for its Anti-Microbial efficiency against G(+)ve bacteria (Streptococcus pyogenes, Staphylococcus aureus), G(-)ve bacteria (Escherichia coli, Klebsiella pneumoniae) and strain of fungi (Candida albicans). Compound (4e) exhibited the highest Anti-Microbial efficiency against both strains G(-)ve and G(+)ve bacteria. Additionally, compound (4b) exhibits a good action for both strains. All synthesized compounds exhibit high antifungal activity against candida albicans when compared to the standard compound, fluconazole. FT-IR and 1H-NMR spectroscopy were utilized for the characterization of the final compounds.